Effects of dietary lipid sources on growth performance and carcass traits in Pekin ducks - X. Ao; I.H. Kim (Poultry Science, 2020)
ABSTRACT: This study was conducted to determine the influence of dietary lipid sources on growth performance, carcass traits and taste scores in Pekin ducks. A total of 1,500 fifteen-day-old ducks (820 ± 22 g) were blocked based on body weight (BW), and randomly allotted to 3 treatments with 10 replicates of 50 birds each (25 males and 25 females). The experiment lasted for 4 wk, and dietary treatments included 3 different lipid sources (soybean oil, duck fat, and palm oil), which were evaluated in corn-soybean meal diets (3250 kcal/kg metabolizable energy and 16.5% crude protein for grower diet and 3350 kcal/kg metabolizable energy and 15.5% crude protein for finisher diet). During days 15 to 28, feeding soybean oil and palm oil diets increased (P < 0.05) body weight gain (BWG), but decreased (P < 0.05) feed intake, feed-to-gain ratio (F/G) and caloric conversion compared with duck fat. During days 29 to 42, birds fed duck fat diet had higher BWG, but lower (P < 0.05) F/G and caloric conversion than those fed soybean oil and palm oil diets. Overall, feeding soybean oil diet increased (P < 0.05) BWG and final BW, but decreased (P < 0.05) F/G compared with palm oil. Birds fed duck fat diet had higher (P < 0.05) skin, subcutaneous fat and abdominal fat yield compared with palm oil. Left breast meat yield in soybean oil group was higher (P < 0.05) than that in duck fat and palm oil groups. Birds in soybean oil group had lower (P < 0.05) roasting loss, but higher (P < 0.05) comprehensive score compared with duck fat and palm oil. In summary, birds fed soybean oil diet had the best growth performance and taste scores for roasting, whereas the duck fat was better in abdominal fat and subcutaneous fat yield than soybean oil and palm oil in Pekin ducks from 15 to 42 d of age under the same nutritional level.